Uji Aktivitas Antibakteri Ekstrak Etanol Daun Seroja (Nelumbo nucifera Gaertn.) terhadap Escherichia coli dan Staphylococcus aureus - Khairani Fitri; Tetty Noverita Khairani; Ruth Mayana Rumanti; Sri Handayani; Mintaria Halawa (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: The increasing occurrence of bacterial infections and antimicrobial resistance has encouraged the investigation of medicinal plants as potential sources of antibacterial compounds. Lotus (Nelumbo nucifera Gaertn.) leaves contain several classes of secondary metabolites that may contribute to antibacterial activity. Objective: This study evaluated the antibacterial activity of lotus leaf ethanol extract against Escherichia coli and Staphylococcus aureus and identified the major classes of secondary metabolites present in the extract. Methods: This laboratory experimental study used lotus leaf extract prepared by maceration with 96% ethanol. The simplicia was characterized and subjected to phytochemical screening. Antibacterial activity was evaluated using the paper-disc diffusion method on Mueller–Hinton agar at extract concentrations of 10%, 15%, and 20%, with clindamycin as the positive control and dimethyl sulfoxide as the negative control. Each treatment was tested in triplicate. Inhibition-zone diameters were analyzed using one-way analysis of variance followed by Tukey's HSD test. Results: The lotus leaf material contained alkaloids, flavonoids, saponins, tannins, steroids, and triterpenoids. Against E. coli, the mean inhibition-zone diameters at concentrations of 10%, 15%, and 20% were 13.60, 15.40, and 16.60 mm, respectively; the corresponding values against S. aureus were 14.56, 15.21, and 18.13 mm. Differences among treatments were statistically significant for both test bacteria (p<0.001). Conclusion: Lotus leaf ethanol extract exhibited concentration-dependent antibacterial activity against E. coli and S. aureus, with the strongest inhibition observed at 20%. Further studies should determine the minimum inhibitory and bactericidal concentrations and characterize the active antibacterial constituents.